Hubungan Jenis Dinding dan Atap dengan Suhu dan Kelembaban Rumah Pada Pemukiman Lahan Basah - Muhammad Farid Abdurrahman; Imam Santoso; Erminawati Erminawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
The wetland settlements are swamp ecosystems including peat swamps which are affected by fresh and brackish water. One of the characteristics of wetlands has low elevation and affected by tides. The purpose of this study was to determine the relationship between the type of wall and roof with the temperature and humidity of the house in the wetland settlement in Desa Tamban Lupak Kecamatan Kapuas Kuala Kabupaten Kapuas. Research design with Cross Sectional Study. The sample in this study totaled 58 housing units. Data analysis using the Spearman –rho correlation test. Statistical test results showed the type of wall with house temperature has no relationship with the Sig. (2-tailed) = 0.439> α = 0.05. The type of roof with house temperature has no relationship with the Sig. (2-tailed) = 0.204> α = 0.05. The type of wall with house humidity has no relationship with the Sig. (2-tailed) = 0.767> α = 0.05. The type of roof with house humidity has no relationship with the value of Sig. (2-tailed) = 0.099> α = 0.05. This study showed that there was no relationship between the type of wall and roof with the temperature and humidity of the house in a wetland settlement.